Lymph node ratio: prognostic value in laryngeal cancer after primary total laryngectomy - Mónica Teixeira; Joana Freitas Rebelo; Elisabete Torres Branco; Nuno Medeiros; Sandra Alves; Pedro Oliveira (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objectives: To evaluate Lymph node ratio (LNR) as a predictor for survival and recurrence of laryngeal cancer with metastatic lymph nodes (pN+).